Question
upstudy study bank question image url

29.) \( 15 m=45 \) 36.) \( 2 m=124 \) 30.) \( 7 d=56 \) 37.) \( 14 r=42 \) 31.) \( 21 x=84 \) 38.) \( \mathbf{2 9 t}=77 \) 32.) \( 9 y=63 \) 39.) \( 9 x=143 \) 33.) \( \frac{2}{7} x=8 \) 40.) \( \frac{1}{2} v=10 \) 34.) \( \frac{3}{5} z=12 \) 41.) \( \frac{2}{3} c=8 \) 35.) \( \frac{4}{6} z=7^{1 / 3} \) 42.) \( \frac{3}{4} c=51 / 4 \)

Ask by Ingram Tyler. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the solutions to each equation: 29.) m = 3 30.) d = 8 31.) x = 4 32.) y = 7 33.) x = 28 34.) z = 20 35.) z = (3⁄2)·7^(1⁄3) 36.) m = 62 37.) r = 3 38.) t = 77⁄29 39.) x = 143⁄9 40.) v = 20 41.) c = 12 42.) c = 17

Solution

We have a list of separate equations. (Even though some of the same letters appear more than once, each equation is to be solved on its own.) One acceptable set of solutions is as follows: 29.) 15m = 45   Divide both sides by 15: m = 45⁄15 = 3 30.) 7d = 56   Divide by 7: d = 56⁄7 = 8 31.) 21x = 84   Divide by 21: x = 84⁄21 = 4 32.) 9y = 63   Divide by 9: y = 63⁄9 = 7 33.) (2⁄7)x = 8   Multiply both sides by 7⁄2: x = 8×(7⁄2) = 56⁄2 = 28 34.) (3⁄5)z = 12   Multiply both sides by 5⁄3: z = 12×(5⁄3) = 60⁄3 = 20 35.) (4⁄6)z = 7^(1⁄3)   Note that 4⁄6 simplifies to 2⁄3. Then: (2⁄3)z = 7^(1⁄3)   Multiply both sides by 3⁄2: z = 7^(1⁄3)×(3⁄2) = (3⁄2)·7^(1⁄3) 36.) 2m = 124   Divide both sides by 2: m = 124⁄2 = 62 37.) 14r = 42   Divide by 14: r = 42⁄14 = 3 38.) 29t = 77   Divide by 29: t = 77⁄29   (This fraction does not simplify further.) 39.) 9x = 143   Divide by 9: x = 143⁄9   (Note: 143 factors as 11×13 and does not cancel with 9.) 40.) (1⁄2)v = 10   Multiply both sides by 2: v = 10×2 = 20 41.) (2⁄3)c = 8   Multiply by 3⁄2: c = 8×(3⁄2) = 24⁄2 = 12 42.) (3⁄4)c = 51⁄4   Multiply both sides by 4⁄3: c = (51⁄4)×(4⁄3) = 51⁄3 = 17 Each equation is solved independently, so even though the same variable symbol appears more than once, you have to use the appropriate answer for each separate problem.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Let’s dive into those equations and solve them! For each equation, you can figure out the variable by isolating it. Just remember, to isolate means to get the variable by itself on one side of the equation. For example, in the equation \( 15m = 45 \), you would divide both sides by 15 to find \( m = 3 \). Easy peasy! Finding the value of a variable like \( m \), \( x \), or \( y \) can tell you a lot about real-world scenarios. Let’s say \( m \) represents minutes you need to workout. If you find \( m = 3 \) from the equation \( 15m = 45 \), then you know you’re putting in a good effort—even if those minutes are just the warm-up! Join the math while living your daily life—it makes the numbers a lot less daunting!

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy